The Effect of Dietary Probiotic and Oxygen Supply on the Growth and Survival Rate of Eels (Anguilla bicollor) - Gagan Garnawansah; Dian Permana; Dasep Hasbullah; Zaenal Arifin Siregar; Dzikri Wahyudi; Boyun Handoyo; Indrian Rizka Amalia; Ratna Indria Sari (Postgraduate, University of Mataram, 2025)
The aquaculture of Anguilla bicollor has significant economic potential, but persistent challenges continue to hinder profitability for farmers. Two of the most pressing issues are low dissolved oxygen levels and poor feed conversion efficiency. These problems slow eel growth and drive-up operational costs, creating a bottleneck for sustainable production. This study examines a combined strategy to tackle these challenges by integrating probiotics (Lactobacillus sp.) and paddlewheel aeration. Research was conducted at BLUPPB Karawang, using 600 juvenile eels in ponds subjected to four distinct treatments: (1) probiotics and paddlewheels together, (2) paddlewheels-only, (3) probiotics-only, and (4) a control group with no intervention. Over a 45-day period, survival rates (SR), relative growth rates (RGR), and feed conversion ratios (FCR) were carefully monitored. The findings were promising. Ponds that used both probiotics and paddlewheels achieved the best results: an RGR of 1.19%, an SR of 100%, and an FCR of 1.09. Probiotics contributed to better gut health and digestion, while the paddlewheels boosted water oxygenation—creating an ideal growth environment. While no direct interaction between the two methods was observed, their combined application proved highly effective in improving productivity and sustainability. This integrated approach offers a practical solution to some of the most significant challenges in Anguilla bicollor aquaculture.